2009
DOI: 10.4037/ajcc2009938
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Use of Indwelling Urinary Catheters and Associated Urinary Tract Infections

Abstract: Background Use of indwelling urinary catheters can lead to complications, most commonly catheter-associated urinary tract infections. Duration of catheterization is the major risk factor. These infections can result in sepsis, prolonged hospitalization, additional hospital costs, and mortality. Objectives To implement and evaluate the efficacy of an intervention to reduce catheter-associated urinary tract infections in a medical intensive care unit by decreasing use of urinary catheters. Methods Indications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 22 publications
4
80
1
4
Order By: Relevance
“…However, similar to other studies [23,30], we found its use in the context of this study of limited value, as it failed to reflect important practice changes. Comparable intervention studies show similar results with respect to catheter use and CAUTI rate [6,11]; despite fewer catheter days [31] or reduced duration of inappropriate urinary catheterization [10], the CAUTI rate is not always reduced. This may be explained by how the CAUTI rate is calculated [3], i.e.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, similar to other studies [23,30], we found its use in the context of this study of limited value, as it failed to reflect important practice changes. Comparable intervention studies show similar results with respect to catheter use and CAUTI rate [6,11]; despite fewer catheter days [31] or reduced duration of inappropriate urinary catheterization [10], the CAUTI rate is not always reduced. This may be explained by how the CAUTI rate is calculated [3], i.e.…”
Section: Discussionmentioning
confidence: 63%
“…Nurses are therefore in a key position to influence decisions about the insertion, continuing use and removal of catheters [11]. However, as they may base their decisions on personal preference rather than evidence-based guidelines [16] and existing routines within their practice, it is of the utmost importance to engage nurses and raise their awareness about evidence-based recommendations for preventing CAUTIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific recommendation for the appropriate urinary catheter use (category IB) is: "Minimize urinary catheter use and duration of use in all patients, particularly those at www.intechopen.com Clinical Management of Complicated Urinary Tract Infection 8 higher risk for CAUTI or mortality from catheterization such as women, the elderly, and patients with impaired immunity" (Gould et al, 2009). In this contest, a recent study (Elpern et al, 2009) has been conducted in a medical ICU in order to implement and evaluate the efficacy of an intervention, based on the decreasing use of urinary catheters, to reduce CAUTI. Results of this study report that the implementation of an intervention targeting the appropriate use of indwelling urinary catheters may result in a significant reduction in the duration of catheterization as well as in the occurrences of CAUTIs.…”
Section: Prevention Of Cautimentioning
confidence: 99%
“…Use of urinary catheters in the ICU causes breaches in the mucosa or may provide a surface for colonization, thus, increasing the incidence of CAUTI. The risk for infection is at least 5% per day of catheterization (Tissot et al, 2001;Elpern et al, 2009). Other factors have been reported as potential risk factors for CAUTI including constitutional factors such as female gender, pregnancy and older age and potential modifiable factors such as poor nutrition, fecal incontinence, use of systemic antibiotics, severity of illness, impaired immune system function, and elevated creatinine level (Gray, 2010).…”
mentioning
confidence: 99%